Attachment Styles, Condomless Sex, and Drugs in HIV-Positive Gay and Bisexual Men. Issue 1 (2nd January 2020) - Fumaz, Carmina R.; Muñoz-Moreno, Jose A.; Ferrer, Maria Jose; Ornelas, Arelly; Coll, Josep; Clotet, Bonaventura
Abstract: This study evaluated whether attachment styles might be related to condomless sex, use of drugs, and adherence to antiretroviral treatment (ART) in 400 HIV-positive gay and bisexual men (GBM). With the Relationship Questionnaire, 160 men were classified as securely attached and 240 as insecurely attached (88 dismissive, 79 preoccupied, and 73 fearful). Insecurely attached GBM had more condomless sex ( p  = 0.04), and used more cocaine ( p  = 0.001), ecstasy ( p  = 0.03), GHB ( p  = 0.04), and ketamine ( p  = 0.04). No differences were observed in adherence to ART. Dismissively attached GBM reported more condomless sex and use of drugs than preoccupied and fearfully attached GBM. The perspective of attachment might enrich the interventions to promote heath care in GBM.